Burden of norovirus in healthcare facilities and strategies for outbreak control. Issue 4 (April 2015) - Kambhampati, A.; Koopmans, M.; Lopman, B.A.
Summary: Norovirus is the most frequently occurring cause of community-acquired acute gastroenteritis in people of all ages. It is also one of the most frequent causes of outbreaks in healthcare settings, affecting both long-term care facilities and acute care hospitals. Whereas norovirus gastroenteritis is typically mild and resolves without medical attention, healthcare-associated infections often affect vulnerable populations, resulting in severe infections and disruption of healthcare services. Globally, most norovirus outbreaks in hospitals and residential care institutions are associated with genogroup II type 4 (GII.4) strains. Recent data demonstrate that excess mortality occurs during outbreak periods in healthcare facilities. Nosocomial outbreaks can result in large economic and societal costs. Current control measures for norovirus are largely based on general infection control principles, and treatment is mainly supportive and non-specific. While neither vaccines nor antiviral agents are currently available, both are being developed with encouraging results.